DESCRIPTION OF KNOWLEDGE AND BEHAVIOR OF THE ACADEMIC COMMUNITY IN DISPOSING OF GARBAGE IN THE ENVIRONMENT OF NUSA CENDANA UNIVERSITY - ., Salsabila; Handoyo, Nicholas (Universitas Nusa Cendana, 2024)
Nusa Cendana University Kupang has attempted to provide cleaning facilities, but the condition of the campus environment is still dirty due to the behavior of students who litter. If students are not in the campus environment, the campus environment becomes clean. This study examines the knowledge and behavior of waste management in the environment of Nusa Cendana University (UNDANA) Kupang City. This study used a qualitative phenomenological approach with a semi-structured interview method, with 12 participants consisting of lecturers, students, staff, and cleaning service. The results of this study found four main themes: knowledge, awareness, conformity, and facilities. It was found that the knowledge of the academic community about waste management is very low, awareness to maintain cleanliness is low, and social conformity from family and friends also influences negative behavior. In addition, waste bin facilities on campus are still inadequate and unmaintained. This study suggests the need for increased education, improved facilities, and social approaches to increase awareness and waste management behavior among the UNDANA academic community.